Tailoring perovskite ceramics for improved structure, vibrational behaviors and radiation protection: The role of lanthanum in PbTiO3 - Almousa N.; Issa S.A.M.; Salem M.M.; Darwish M.A.; Serag E.N.; Nazrin S.N.; Zakaly H.M.H. (Elsevier B.V., 2025)
This study investigates the characteristics of lanthanum (La)-doped lead titanate (PbLaxTi(1-3x/4)O3 where, x = 0.0, 0.02, 0.04, 0.06, 0.08, and 0.1), a type of perovskite ceramic. It specifically focuses on analyzing its structure, vibrational properties, and efficacy in shielding against radiation. The prepared samples are investigated by X-ray diffraction (XRD), which clarified that the small doping of La (x 0.06) produced the required phase, and increasing the La doping (x > 0.06) produced nonrequired phases (secondary phase). Also, increasing the La doping converted the crystal symmetry from tetragonal to cubic, which was confirmed by the tetragonality raio (c/a) calculations. Also, the samples are investigated by Fourier transform infrared (FTIR) spectroscopy to confirm the XRD results. Transmission electron microscopy (TEM) examination clarified that the prepared samples were in the nanoscale range with a maximum crystallite size value of around 70 nm. In addition, the shielding effectiveness of all the prepared samples was theoretically evaluated using the Phy-X/PDS program by considering characteristics such as the linear attenuation coefficient (GLAC), mean free path (GMFP), transmission factor (TF), and radiation protection efficiency (RPE). Increasing the La concentration increases the theoretical density to 4.98 gm/cm3 at x = 0.1, leading to low TF and GMFP values and high GLAC values. This produces samples with high attenuation to radiation and high shielding effectiveness. ? 2024 Elsevier B.V.